Research progress in the treatment of non-scarring alopecia: mechanism and treatment - Guo, Rui-Xian; Zhao, Yong-Kang; Hu, Ke-Jian; Jia, Kun-Mu; Shi, Wei; Yi, Yan-Xiao; Gong, Hai-Ying; Wang, Jia-Bo; Gao, Yuan (Frontiers in Pharmacology, 2025)
IntroductionNon-scarring alopecia, encompassing androgenetic alopecia (AGA), alopecia areata (AA), and telogen effluvium (TE), is a common skin condition that significantly impacts both the physical and psychological wellbeing of affected individuals. This review aims to delve into the multifactorial etiology of non-scarring alopecia and to critically assess the current and emerging treatment options available for management.MethodsThe review methodology involved a comprehensive literature search in PubMed and Web of Science, focusing on the genetic, environmental, and psychological factors that contribute to the development of non-scarring alopecia. The search included studies published from 2004 to 2024, primarily in English, to incorporate both foundational and recent advancements in the field. The inclusion criteria encompassed clinical trials, meta-analyses, and high-quality observational studies investigating the pathogenesis and treatment of non-scarring alopecia. Case reports, editorials, and studies with insufficient methodological details were excluded. Additionally, this review evaluated FDA-approved treatments (e.g., minoxidil and finasteride) and emerging therapeutic agents, such as Janus kinase (JAK) inhibitors and natural remedies, with an emphasis on their mechanisms, efficacy, and safety profiles.ResultsThe findings from this review indicate that the currently available treatments, such as topical and oral minoxidil, oral finasteride, and Janus kinase (JAK) inhibitors, exhibit limited efficacy and are associated with adverse effects. In contrast, natural remedies have shown promise as alternative treatments, potentially offering more effective management with fewer side effects.DiscussionThe conclusion drawn from this review is that there is a significant potential for natural products and innovative drugs to provide effective treatment options for non-scarring alopecia. However, the assumption that natural remedies universally have fewer side effects than conventional treatments requires careful consideration, as their safety profiles vary. This underscores the need for further research and development in this area to improve patient outcomes and quality of life.